Circadian Rhythm in Cytokines Administration - A. Trufakin, Valery; V. Shurlygina, Anna (Mini Reviews in Medicinal Chemistry, 2016)
In recent times, a number of diseases involving immune system dysfunction have appeared. This increases the importance of research aimed at finding and developing optimized methods for immune system correction. Numerous studies have found a positive effect in using cytokines to treat a variety of diseases, yet the clinical use of cytokines is limited by their toxicity. Research in the field of chronotherapy, aimed at designing schedules of medicine intake using circadian biorhythms of endogenous production of factors, and receptors’ expression to the factors on the target cells, as well as chronopharmacodynamics and chronopharmacokinetics of medicines may contribute to the solution of this problem. Advantages of chronotherapy include a greater effectiveness of treatment, reduced dose of required drugs, and minimized adverse effects. This review presents data on the presence of circadian rhythms of spontaneous and induced cytokine production, as well as the expression of cytokine receptors in the healthy body and in a number of diseases. The article reviews various effects of cytokines, used at different times of the day in humans and experimental animals, as well as possible mechanisms underlying the chronodependent effects of cytokines. The article presents the results of chronotherapeutic modes of administering IL-2, interferons, G-CSF, and GM-CSF in treatment of various types of cancer as well as in experimental models of immune suppression and inflammation, which lead to a greater effectiveness of therapy, the possibility of reducing or increasing the dosage, and reduced drug toxicity. Further research in this field will contribute to the effectiveness and safety of cytokine therapy.
Keywords: drug toxicity